Effects of sodium arsenite exposure on behavior, ultrastructure and gene expression of brain in adult zebrafish (Danio rerio) - Hao Ma; Wenjing Yang; Yang Li; Jing Li; Xiyue Yang; Yunyan Chen; Yifan Ma; Dianjun Sun; Hongna Sun (Ecotoxicology and Environmental Safety, 2024)
Arsenic, a common metal-like substance, has been demonstrated to pose potential health hazards and induce behavioral changes in humans and rodents. However, the chronic neurotoxic effects of arsenic on aquatic animals are still not fully understood. This study aimed to investigate the effects of arsenic exposure on adult zebrafish by subjecting 3-month-old zebrafish to three different sodium arsenite water concentrations: 0 μg/L (control group), 50 μg/L, and 500 μg/L, over a period of 30 days. To assess the risk associated with arsenic exposure in the aquatic environment, behavior analysis, transmission electron microscopy techniques, and quantitative real-time PCR were employed. The behavior of adult zebrafish was evaluated using six distinct tests: the mirror biting test, shoaling test, novel tank test, social preference test, social recognition test, and T maze. Following the behavioral tests, the brains of zebrafish were dissected and collected for ultrastructural examination and gene expression analysis. The results revealed that sodium arsenite exposure led to a significant reduction in aggression, cohesion, social ability, social cognition ability, learning, and memory capacity of zebrafish. Furthermore, ultrastructure and genes regulating behavior in the zebrafish brain were adversely affected by sodium arsenite exposure.